Studi Penanggulangan Banjir Dengan Upaya Normalisasi Pada SUngai Sragi Baru Kabupaten Pekalongan Provinsi Jawa Tengah - Roosydi, Yayan Ishad; Priyantoro, Dwi; Sisinggih, Dian (Fakultas Teknik, Universitas Brawijaya, 2023)
Sragi Baru River is located in Pekalongan Regency, Central Java Province with a main river length of 60 km. This river is located in Sragi Baru watershed with an area of 254 km2. The cross-sectional capacity of Sragi Baru River is inadequate due to the influence of sedimentation. In this study, the first thing to do was to analyze the design flood discharge, and to model using HEC-RAS 5.0.7 with the analyzed design flood discharge of 644,465 m3 / s. Cross-sectional capacity planning considers the concentration of debris charge in the flow discharge, so that the plan discharge QP = 1.1 Ã— Q25th = 708.912 m3/s. Repairs to the cross-section of the river were carried out with a trapezoidal double cross section with a talud slope of 1:1.5, and eliminated the sediment that occurred so that the Manning roughness coefficient changed to 0.018, and the elongated slope of the river was planned to be 0.00027. Then for the embankment, the ground is planned with a freeboard 1 m, a lighthouse width of 4 m, and a slope of 1: 1.5. Furthermore, The influence of sedimentation on Sragi Baru River results in flood-prone conditions that will occur in the 20 years. In this case, the volume of the resulting deposit amounted to 299,667,311 m3, and the slope became 0.000304. Therefore, it is necessary to carry out river normalization activities in the form of dredging the riverbed to restore cross-sectional capacity to be able to drain the planned flood discharge (QP = 708.912 m3 /s).Sungai Sragi Baru berlokasi di Kabupaten Pekalongan, Provinsi Jawa Tengah dengan Panjang sungai utama 60 km. Sungai ini berada pada DAS Sragi Baru dengan luas 254 km2. Kapasitas penampang Sungai Sragi Baru kurang memadai karena akibat dari pengaruh sedimentasi. Pada studi ini, hal yang pertama dilakukan adalah menganalisis debit banjir rancangan, dan melakukan pemodelan menggunakan HEC-RAS 5.0.7 dengan debit banjir rancangan yang telah dianalisis sebesar 644.465 m3/dt. Perencanaan kapasitas penampang mempertimbangkan konsentrasi muatan debris dalam debit aliran, sehingga debit rencana QP = 1,1 Ã— Q25th = 708,912 m3/dt. Perbaikan penampang sungai dilakukan dengan penampang ganda berbentuk trapesium dengan kemiringan talud 1:1,5, dan menghilangkan endapan yang terjadi sehingga koefisien kekasaran Manning berubah menjadi 0,018, dan kemiringan memanjang sungai direncanakan 0,00027. Lalu untuk tanggul urugan tanah direncanakan dengan tinggi jagaan 1 m, lebar mercu 4 m, dan kemiringan 1:1,5. Selanjutnya dilakukan analisis sedimentasi. Pengaruh sedimentasi pada Sungai Sragi Baru mengakibatkan kondisi rawan banjir yang akan terjadi setelah 20 tahun. Dalam hal ini, volume endapan yang dihasilkan sebesar 299.667,311 m3, dan slope menjadi 0.000304. Oleh karena itu, perlu dilakukan kegiatan normalisasi sungai berupa pengerukan dasar sungai untuk mengembalikan kapasitas penampang agar mampu mengalirkan debit banjir rencana (Qp = 708,912 m3/dt).Â